2004
DOI: 10.1111/j.1442-9071.2004.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year follow up of selective laser trabeculoplasty in Chinese eyes

Abstract: With fewer medications, SLT gives similar intraocular pressure reduction to medical therapy alone in Chinese patients with primary open-angle glaucoma or ocular hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 19 publications
6
97
2
2
Order By: Relevance
“…There was a trend toward more treatment steps necessary for adequate IOP control in the medication arm with 27% requiring additional drops compared to 11% in the SLT group receiving additional laser [8]. Other prospective studies have been done which corroborate with our findings [86][87][88].…”
Section: Selective Laser Trabeculoplasty As Initial Treatmentsupporting
confidence: 82%
“…There was a trend toward more treatment steps necessary for adequate IOP control in the medication arm with 27% requiring additional drops compared to 11% in the SLT group receiving additional laser [8]. Other prospective studies have been done which corroborate with our findings [86][87][88].…”
Section: Selective Laser Trabeculoplasty As Initial Treatmentsupporting
confidence: 82%
“…In a study by Lai et al, 11 17.2% of the patients with POAG or ocular hypertension required trabeculectomy after SLT despite maximal medications. The observations in the PG eyes, including more complications, decreasing IOP-lowering effect after 6 months, and more need for further surgical interventions, may indicate that SLT is less efficient in PG eyes compared with PEX and POAG eyes.…”
Section: Discussionmentioning
confidence: 98%
“…All such reductions were statistically significantly lower than baseline. Although the effect of SLT may be greatest immediately after treatment 15,16 because of the increase in porosity of the trabecular meshwork from the upregulation of metalloproteinases, cytokines, and macrophages, 17 the lower IOP on day 1 post SLT may also be contributed in part to a falsely low IOP reading resulting from alterations in corneal hysteresis from the subclinical corneal edema. It has been demonstrated that corneal edema after phacoemulsification has been associated with a relatively lower IOP by Goldmann applanation tonometry because of the reduction of corneal hysteresis and alterations of the stromal lamellar architecture.…”
Section: Discussionmentioning
confidence: 99%